Effects of a 1-Day Training Course in Dermoscopy Among General Practitioners - Anna Augustsson; John Paoli (Mattioli1885, 2019)
Background: General practitioners (GPs) are often the first point of contact for Swedish patients seeking medical advice for skin lesions of concern, but many lack training in dermoscopy. Objective: To examine the effects of a 1-day training course in dermoscopy among Swedish GPs. Methods: The intervention group consisted of GPs who underwent a 1-day training course in dermoscopy and a control group that did not undergo any education. Before the training course, the intervention group performed a test consisting of 30 dermoscopy cases including 9 different benign and malignant melanocytic and nonmelanocytic diagnoses. The participants then took the same test directly after the course and again after 6 months. The control group took the same test twice with a 6-month interval in between tests in order to avoid recall bias. Results: Twenty-seven GPs in the intervention group took the test before and immediately after the course with an improvement of their median test scores by 8 points (13 vs 20 correct answers, P < 0.01). Eighteen participants also took the test a third time after 6 months with similar results compared with the second test (median scores of 20.5 vs 20.0, P = 0.3). In the control group, 16 persons preformed both tests with an improvement of their median score by 2 points (13.5 vs 15.5 correct answers, P = 0.06). Conclusions: The results of this study show positive effects on diagnostic accuracy in a test situation among GPs receiving a 1-day training course in dermoscopy.